The Specific Characteristics and Structure of Knowledge Workers in the Polish IT Sector - Results of Preliminary Self-assessment Research - Anna PIETRUSZKA-ORTYL (Communications of International Proceedings, 2021)
Knowledge workers - professionals whose activity is based on the conversion of information into knowledge and knowledge-based products – constitute the foundations of the networked civilization constituting the technological basis of the new economy. These are corporate digital nomads whose knowledge constitutes the core of the organizations with which they are associated. The IT sector is a branch of industry in which the main source of competitive advantage is primarily the expertise of highly qualified experts - professionals understood in terms of knowledge workers. Hence, its main attribute is a strong demand for employee-specialists and an orientation towards converting personalized knowledge into organizational knowledge. The aim of the study was to describe the structure of intellectual employees in the IT sector. Based on the proposed classification, the author discusses the specifics of particular sub-professions of knowledge workers in the surveyed industry, and also presents the detailed features of their positions as well as the different types of high-context, personalized knowledge. The research showed that the majority of the respondents operate in accordance with a specialist knowledge-based work model and usually perform the role of linkers, networkers and learners. Their knowledge usually takes the form of personalized, often tacit know-how, -who, -why and -when. As a consequence, based on the four-degree scale used to measure the development of professionalism in a society, the intellectual employees of the Polish IT environment interviewed in the research represent, for the most part, examples of the third stage.
Keywords: Knowledge Work; Cognitarians; IT Sector; Professional Typology